Efficacy and Satisfaction among HER2 Positive Breast Cancer Patients Undergoing Subcutaneous Injection of PHESGO along with Chemotherapy: A Case Series - Nag, Shona; Mane, Anupama; Dhobale, Madhuri; Varghese, Kavitha; Patra, Abhilash; Pant, Hira B; Agiwal, Varun; A Y, Nirupama; Murthy, G V S (Asian Pacific Journal of Environment and Cancer, 2024)
Background: The prevalence of Human Epidermal Growth Factor Receptor 2 positive (HER2+) breast cancer (BC) in India ranged from 11% to 17%. A combination of intravenous (IV) pertuzumab, trastuzumab and docetaxel in HER2+ BC reported a significant increase in the overall survival rate. However, the time taken for infusion of these drugs is lengthy. PHESGO, a combination of these two drugs along with hyaluronidase is provided subcutaneously and the time taken is 5-8 minutes. Despite patient preference for PHESGO, its efficacy and satisfaction levels in the Indian context remain unexplored. This case series investigates the efficacy of PHESGO with chemotherapy and assesses the level of satisfaction reported by HER2+ BC patients. Methods: HER2+ BC patients were identified retrospectively from January 2022 to November 2023. Interviews during follow-ups assessed patient satisfaction. Efficacy was evaluated based on Positron Emission Tomography (PET) scans for metastatic/adjuvant settings and pathological complete response (pCR) rate for neoadjuvant cases. Results: In total 27 HER2+ BC patients received PHESGO treatment with a median age of 54.5 years. Patients who received PHESGO with chemotherapy in neoadjuvant and metastatic settings were 44.4% and 51.9% respectively. The median cycle of PHESGO with chemotherapy was 5. Neoadjuvant patients showed an 83.3% pCR rate, while 85.7% of metastatic patients reported partial response after three cycles. Among 25 patients, 92% were satisfied with subcutaneous administration of PHESGO. Conclusion: The findings support the potential of PHESGO as an effective and convenient treatment option for HER2+ BC patients. However, further research, including larger prospective studies and long-term follow-ups, is warranted to comprehensively evaluate the safety profile, quality of life, and comparative effectiveness of PHESGO versus intravenous administration.